My first picture book of baby animals - Cloke, Rene (illustrator) (London, Award Publications., 1990)
Briefly describes physical characteristics and habits of sixteen animals and their young, including the pine marten, lynx, raccoon, hedgehog, grizzly bear, otter, grey squirrel, fox, opossum, and prairie dog.